2020
DOI: 10.1371/journal.pone.0235008
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of index partner HIV self-testing among HIV-positive clients in Malawi: A mixed methods analysis

Abstract: We sought to evaluate whether HIV-positive adults in Malawi were willing to distribute HIV self-testing (HIVST) kits to their sexual partners of unknown HIV status (index HIVST). Design A mixed-methods study was nested within a larger HIVST trial conducted at 15 health facilities in Malawi. Exit surveys were conducted with HIV-positive adults during routine outpatient department visits to assess perceived acceptability of index partner HIVST versus standard partner referral slips that request partner(s) to att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Nearly all studies concluded that HIV-ST was perceived easy to use [23, 28, 30-32, 35, 38, 40, 42, 44, 46, 47, 49, 57, 61, 63, 68, 70, 74, 77, 80, 82, 83, 85, 127, 130-134, 141]. Most studies 107,113,114,119,121,[183][184][185][186][187][188][189][190] and six observational mixed method studies [126,129,136,138,191,192]. While adoption is distinct from appropriateness, we found that qualitative results for adoption overlapped with results for appropriateness and we opted to report them together (with acceptability) in the next section.…”
Section: Acceptabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Nearly all studies concluded that HIV-ST was perceived easy to use [23, 28, 30-32, 35, 38, 40, 42, 44, 46, 47, 49, 57, 61, 63, 68, 70, 74, 77, 80, 82, 83, 85, 127, 130-134, 141]. Most studies 107,113,114,119,121,[183][184][185][186][187][188][189][190] and six observational mixed method studies [126,129,136,138,191,192]. While adoption is distinct from appropriateness, we found that qualitative results for adoption overlapped with results for appropriateness and we opted to report them together (with acceptability) in the next section.…”
Section: Acceptabilitymentioning
confidence: 99%
“…Proper kit design for the target population was often mentioned. Design considerations included the instructional materials [90, 98, 100, 103, 107, 114, 120, 124, 131-133, 187, 190, 201-203] and the type of fluid (blood or oral fluid) [90,92,100,102,104,106,108,110,114,116,119,124,127,131,132,137,139,184,191,196]. Instructions needed to be clear and easy to understand.…”
Section: Positive Perceptions On Hiv-stmentioning
confidence: 99%
See 1 more Smart Citation
“…For implementers, the design of our demonstration study can be patterned to future programs on HIVST that are tailored to other local MSM and TGW communities in the Philippines. HIVST is said to increase HIV testing [47, 55, 56] among key populations; thus, implementers should include HIVST as one of the key indicators in their existing HIV Testing and Counselling Services (HTS). Lastly, funding agencies or companies may consider HIVST their Corporate Social Responsibility (CSR) service by helping the community as potential sustainable funding sources [57].…”
Section: Discussionmentioning
confidence: 99%
“…3 4 Safety, a major concern from the outset, was demonstrated through extensive social science research, confirming minimal social and physical harms. [5][6][7] Outcomes of HIVST research have also focused on 'real-world' implementation and relevance to policymakers, with randomised trials assessing linkage to HIV treatment, HIV prevention services for those who test HIV-negative and cost-effectiveness. 8 Research on how populations want HIVST delivered, coupled with lessons learnt from implementation and evaluation, has informed scale-up in many high burden settings.…”
Section: What Are the Key Lessons Learnt From Hivst?mentioning
confidence: 99%